1997
DOI: 10.1073/pnas.94.7.2987
|View full text |Cite
|
Sign up to set email alerts
|

Gene 4 helicase of bacteriophage T7 mediates strand transfer through pyrimidine dimers, mismatches, and nonhomologous regions

Abstract: In bacteriophage T7 the gene 2.5 singlestranded DNA-binding protein and the gene 4 helicase together promote the annealing of homologous regions of two DNA partners to form a joint molecule and subsequent strand transfer. In this reaction T7 gene 2.5 protein is essential for joint molecule formation, but is not required for T7 gene 4 protein-mediated strand transfer. T7 gene 4 helicase alone is able to mediate strand transfer, provided that a joint molecule is available. The present paper shows that, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The RecBCD protein, a major enzymatic component of one of E. coli's recombination pathways, is inactivated by T7 soon after infection to allow the phage genome to escape devastation from RecBCD's exonuclease V activity (53). Recently it has been found that T7 single-strand-DNA binding protein and the helicase encoded by gene 4 play major roles in annealing complementary DNA strands together (16,19,20). Thus, formation of single-stranded DNA and annealing of those strands to form heteroduplexes may figure prominently in T7 recombination (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RecBCD protein, a major enzymatic component of one of E. coli's recombination pathways, is inactivated by T7 soon after infection to allow the phage genome to escape devastation from RecBCD's exonuclease V activity (53). Recently it has been found that T7 single-strand-DNA binding protein and the helicase encoded by gene 4 play major roles in annealing complementary DNA strands together (16,19,20). Thus, formation of single-stranded DNA and annealing of those strands to form heteroduplexes may figure prominently in T7 recombination (42).…”
mentioning
confidence: 99%
“…Bacteriophage T7 has provided a powerful tool with which to study DNA replication and offers several advantages as an experimental system. The genetics of T7 are well developed, and a considerable amount is known about the biochemistry of T7 enzymes involved in DNA metabolism (5,6,16,40,46). Efficient in vitro systems for DNA replication and DNA packaging have been developed (9,21,29).…”
mentioning
confidence: 99%
“…Presumably these interactions explain why coordination of leading-and laggingstrand synthesis in vitro is dependent upon gene 2.5 protein (159). Furthermore, gp2.5 facilitates homologous DNA base pairing, a process that is important in the formation of T7 concatemers, in recombination (185)(186)(187), and in the repair of double-stranded breaks (188). The crystal structure of gp2.5 (189) shows that it has the conserved oligosaccharideoligonucleotide-binding fold (OB-fold) that is common to this group of proteins (190,191).…”
Section: T7 Gene 25 Ssdna-binding Proteinmentioning
confidence: 99%
“…The RecBCD protein, a major enzymatic component of one of E. coli's recombination pathways, is inactivated by T7 soon after infection to allow the phage genome to escape devastation from RecBCD's exonuclease V activity (53). Recently it has been found that T7 single-strand-DNA binding protein and the helicase encoded by gene 4 play major roles in annealing complementary DNA strands together (16,19,20). Thus, formation of single-stranded DNA and annealing of those strands to form heteroduplexes may figure prominently in T7 recombination (42).…”
mentioning
confidence: 99%